Malaysian Nuclear Agency / Nurulsafika Seman - Seman, Nurulsafika (Faculty Of Chemical Engineering, 2022)
This industrial training report of Nurnlsafika binti Seman to undergo an industrial training for duration of 6 months which consist of24 weeks before completing the Diploma courses. Starting industrial training on 21 st February 2022 until 5th August 2022 at Malaysian Nuclear Agency (ANM) which guided by Ms. Norshafarina binti Ismail. The purpose of this program is to fulfil the course to complete the Diploma as well as graduate from the university. The training refers to work experience that is relevant to professional development prior to graduate. In first chapter this report is defining the term of industrial training and description on industrial training objectives. This part explains the details of objectives of industrial training report and industrial report. In second chapter of report is overview of the company and departments. The next chapter describes the summary of the duties and various tasks in weekly of industrial training activities that carried out. The next chapter explain in further detail the experience gained, problem encountered, ethical issues, and health, environmental and sustainability aspect during industrial training. The last chapter concluded about the training throughout these 24 weeks. This training gives students a good experience in handling machine, communicate with people, ethics, and safety. Finally, trainee got opportunities to learn more about polymer science.